Case Report: A 6-Year-Old Girl with Bronchopneumonia and Laryngotracheitis - Fahmi Ilham Hatimi; Salman Alfarisi; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Acute respiratory infections remain a leading cause of morbidity and mortality among children, particularly in developing countries, with bronchopneumonia representing one of the most common manifestations. Simultaneous involvement of the upper and lower respiratory tract, such as bronchopneumonia accompanied by laryngotracheitis, is uncommon but may result in severe respiratory compromise due to upper airway obstruction and impaired pulmonary gas exchange. This case report describes a six-year-old girl who presented with fever, productive cough, hoarseness, noisy breathing, and progressive dyspnea. Physical examination revealed tachypnea, wheezing that later progressed to bilateral crackles, and signs of upper airway obstruction. Laboratory evaluation demonstrated neutrophilic leukocytosis, while chest radiography showed diffuse patchy infiltrates consistent with bronchopneumonia. Soft tissue neck radiography demonstrated subglottic narrowing (steeple sign), supporting the diagnosis of laryngotracheitis. The patient had predisposing factors including undernutrition and incomplete childhood immunization. Management consisted of intravenous antibiotics, systemic corticosteroids, nebulized epinephrine, oxygen therapy, and supportive care. Gradual clinical improvement was observed from the second to the fifth day of hospitalization without complications or recurrence of symptoms. This case emphasizes the importance of early recognition of concurrent upper and lower respiratory tract involvement, followed by comprehensive diagnostic evaluation and prompt treatment to achieve favorable clinical outcomes. Improvement of nutritional status and completion of routine immunization should also be emphasized as essential preventive strategies to reduce the burden of severe respiratory infections in children.